A taxonomic survey of the shallow-water (<150 m) black corals (Cnidaria: Antipatharia) of the Hawaiian Islands - Wagner, Daniel (Frontiers in Marine Science, 2015)
The shallow-water (<150 m) antipatharian fauna of the Hawaiian Archipelago is described and illustrated based on a systematic examination of skeletal spine morphology, polyp morphology, colony branching pattern and in situ photographs. A total of 172 black coral specimens were examined, including all available type material of species previously reported from shallow waters off Hawaiʻi. The examined specimens were assigned to three families (Antipathidae, Aphanipathidae and Myriopathidae), six genera (Antipathes, Cirrhipathes, Stichopathes, Aphanipathes, Acanthopathes and Myriopathes), and eight species: Antipathes griggi Opresko, 2009, Antipathes grandis Verrill, 1928, Cirrhipathes cf. anguina (Dana, 1846), Stichopathes echinulata Brook, 1889, Stichopathes? sp., Aphanipathes verticillata mauiensis Opresko et al., 2012, Acanthopathes undulata (Van Pesch 1914) and Myriopathes cf. ulex (Ellis and Solander 1786). The biogeographical distribution of Hawaiian shallow-water black corals is presented and discussed.